2020
DOI: 10.34172/jre.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intranasal recombinant human interferon alfa 2b as prophylaxis for COVID-19 in patients on a hemodialysis program

Abstract: Introduction: Patients diagnosed with end-stage chronic kidney disease on a hemodialysis program (HDP) represent a risk group for COVID-19. Scientific societies have developed guidelines for the prevention of contagion, but there is no prophylactic medicine in them. Objectives: To describe the safety and efficacy of recombinant intranasal human Interferon alfa 2b as prophylaxis for COVID-19 in patients in an HDP. Patients and Methods: Intervention description through the monitoring of 15 patients in outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Wang demonstrated in a review of patients with COVID-19 the presence of 33 % of leukopenias (44). In other studies, leukopenia has been reported to be between 28.1 % and 68.1 %, depending on the severity of the disease and the underlying pathology, suggesting a possible association between severity of leukopenia and severity of COVID-19 (44)(45)(46)(47). Of the 41 patients with COVID-19 who died, the leukocyte count on admission was: 10.8 ± 6.2 × 10 9 / L, (of these 18 patients had leukocytosis with a white count ≥ 10 × 10 9 / L and only 2 patients had leukocytosis ≥20 × 10 9 / L).…”
Section: Discussionmentioning
confidence: 87%
“…Wang demonstrated in a review of patients with COVID-19 the presence of 33 % of leukopenias (44). In other studies, leukopenia has been reported to be between 28.1 % and 68.1 %, depending on the severity of the disease and the underlying pathology, suggesting a possible association between severity of leukopenia and severity of COVID-19 (44)(45)(46)(47). Of the 41 patients with COVID-19 who died, the leukocyte count on admission was: 10.8 ± 6.2 × 10 9 / L, (of these 18 patients had leukocytosis with a white count ≥ 10 × 10 9 / L and only 2 patients had leukocytosis ≥20 × 10 9 / L).…”
Section: Discussionmentioning
confidence: 87%
“…Large proportions of these drugs have been experimented for the exhibited agonist-receptor interactions with IFNAR2, which could be used alone or in conjunction with other anti-virus drugs for against COVID-19 initiation and progression. 105,106 Several limitations of this study should be cautious. First, the power of the cell-type-level integration analysis is limited by the lack of scRNA-seq data and matched genetic information in each sample for discerning COVID-19-relevant cell types.…”
Section: Discussionmentioning
confidence: 95%
“…Large proportions of these drugs have been experimented for the treatment of severe COVID‐19. For example, the FDA‐approved drugs of INTERFERON ALFA‐2B and INTERFERON BETA‐1B exhibited agonist–receptor interactions with IFNAR2 , which could be used alone or in conjunction with other anti‐virus drugs for against COVID‐19 initiation and progression 105,106 …”
Section: Discussionmentioning
confidence: 99%
“…Large proportions of these drugs have been experimented for the treatment of severe COVID-19. For example, the FDA-approved drugs of INTERFERON ALFA-2B and INTERFERON BETA-1B exhibited agonist-receptor interactions with IFNAR2, which could be used alone or in conjunction with other anti-virus drugs for against COVID-19 initiation and progression[89,90].…”
mentioning
confidence: 99%